(untitled) (Research, Society and Development, 2020)
Objective: to carry out a bibliographic survey on the toxicity profile and antibacterial activity of medicinal plants used in the treatment of respiratory diseases, in order to highlight the main species and chemical constituents, in addition to correlating them with the biological activity of the plants found. Methodology: the study is an integrative literature review, in which the databases established for the research were PubMed, BVS and Science Direct. The descriptors used were Medicinal plants, Respiratory diseases, Phytotherapy, Toxicity and Antibacterial and the defined time frame was from the last 10 years, starting in 2010. Results and Discussion: the final sample consisted of 11 articles and the results obtained were presented in relation to the medicinal species used for the treatment of respiratory diseases, with the phytochemistry of the species and the compounds responsible for biological activity, in addition to the description of the toxicity profile and the antibacterial activity of the plants mentioned in the articles. Only studies addressing the species Pelargonium sidoides, Justicia pectoralis and Luffa operculata presented toxicity studies and data on antibacterial activity. In view of this, these plants exhibited a prevalence of inhibition against gram-positive bacteria, such as Streptococcus pyogenes, and in toxicological tests performed, no toxicity was found. Conclusion: it is necessary to carry out more research with the reported plant species, as there was a shortage of clinical studies and it is also essential that toxicity studies be carried out with plants that did not address this topic.